2022
DOI: 10.3892/etm.2022.11436
|View full text |Cite
|
Sign up to set email alerts
|

TUDCA protects against tunicamycin‑induced apoptosis of dorsal root ganglion neurons by suppressing activation of ER stress

Abstract: The existence of endoplasmic reticulum (ER) stress in neurodegenerative diseases has been well established. Tauroursodeoxycholic acid (TUDCA) is a bile acid taurine conjugate derived from ursodeoxycholic acid, which has been reported to exert cytoprotective effects on several types of cells by inhibiting ER stress. The present study explored the effects of TUDCA on primary cultured rat dorsal root ganglion (DRG) neurons. Cell viability and apoptosis of DRG neurons treated with TUDCA and tunicamycin were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…11 TUDCA is an endogenous bile acid derived from ursodeoxycholic acid. 12,13 Evidence indicates that TUDCA plays a protective role in various diseases. [13][14][15] For example, TUDCA ameliorates glucose tolerance and insulin sensitivity in mice with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 TUDCA is an endogenous bile acid derived from ursodeoxycholic acid. 12,13 Evidence indicates that TUDCA plays a protective role in various diseases. [13][14][15] For example, TUDCA ameliorates glucose tolerance and insulin sensitivity in mice with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Evidence indicates that TUDCA plays a protective role in various diseases. [13][14][15] For example, TUDCA ameliorates glucose tolerance and insulin sensitivity in mice with Alzheimer's disease. 12 Furthermore, a previous study found that TUDCA levels were positively correlated with Parabacteroides in DPN patients, 16 implying that TUDCA might have a vital function in DPN progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation